ANALYSIS OF MATHEMATICAL CONNECTION ABILITY IN LINEAR EQUALIES AND INEQUALITY ONE VARIABLE OF CLASS VII STUDENTS OF SMP DOMICILI VILLAGE NANOWA LEARNING YEAR - Krisdamayanti Bohalima (Afore : Jurnal Pendidikan Matematika, 2023)
This study aims to describe students' mathematical connection abilities, especially in the matter of one-variable linear equations and inequalities. This research uses a type of qualitative research with a descriptive research approach. The informants of this study were 20 students of grade VII junior high school who live in Nanowa Village. The data were analyzed with the steps of data collection, data reduction, data presentation and drawing conclusions. The research instrument used was a test of students' mathematical connection abilities and interviews. The research findings show that: students do not understand the material concept of one-variable linear equations and inequalities, students do not understand the relationship between the concepts of one-variable linear equations and inequalities with other mathematical material topics such as exponents and squares, and in everyday life, students are unable to find the relationship between the procedure for solving linear equations and inequalities of one variable and the procedure for solving other mathematical material. This is because students do not understand the questions, students do not master the previous prerequisite material associated with the questions, students are confused in choosing the right completion procedure and students lack accuracy in carrying out arithmetic operations so they often make calculation errors. From these results and findings it can be concluded that students' mathematical connection abilities in the matter of linear equations and inequalities of one variable are still low. Through this research, it is suggested that students' mathematical connection abilities be further enhanced by working on more questions related to mathematical connections.